Distance computation between convex objects using axis-aligned bounding-box in virtual environment application - Sulaiman, Hamzah Asyrani; Bade, Abdullah; Abdullah, Mohd Harun (2013)
Performing collision detection between convex objects in virtual environment simulation is one of vital problems in computer visualization research area. Given a set of two or more colliding objects, in order to determine the exact point of contact between object we need to undergo various high computation algorithm. In this paper, we describes our current work of determining the precise contact by measuring the distance between near colliding objects in order to maintain the accuracy and improve the speed of collision detection algorithm. Common method determine the distance by checking for vertices and edges point between objects in brute force condition. Compared to our method, by given set of objects in virtual environment world, we find the closest point between near colliding objects and bound the potential colliding area with an Axis-Aligned Bounding-Box. Then, we approximate the distance by measuring the distance of the box itself and hence recognize potential colliding area faster than the common method. Our method proven to most effective and efficient for narrow phase collision detection by removing unnecessary testing and reduced computational cost.